A Research Study of Some Aspects of Accounting Education in California (Book). - Bruns, William J.; Williams, Doyle Z. (The Accounting Review, 1969)
Reviews the book, "A Research Study of Some Aspects of Accounting Education in California," by Donald E. Keller.